ARM TRUSTZONE AS A SECURITY FOR USER INTERACTION ON THE MOBILE PLATFORM - Lukman Santoso; Moh Muthohir; Ahmad Ashifudin Aqham (Journal of Engineering, Electrical and Informatics, 2022)
Smartphones have become an important part of human life until now, apart from making phone calls and other communication functions, smartphones are also used as tools for shopping, conducting banking transactions, and so on. This makes security Software on smartphones becoming more critical. trust execution environment technology was popularized to support care for users if the Operation System is compromised namely trust execution environment ARM TrustZone. This research focuses on User-Interaction and Input/Output audio input user interaction channels and proposes an application-transparent solution to keep the user communication strategy on mobile platforms using ARM TrustZone. This research advantage the ARM TrustZone to bring a defended architecture for User Interface input for user interaction channels (T-User-Interaction) and Audio-Input/Output for VoIP calls (T-VoIP-C). The main objective is to establish that the architecture is clear for cellular utilization. All along trust execution environment-established research, one of the critical objections faced was the ability to safely prototype designs. In a trust execution environment study, it is generally necessary to cross hardware factors with the trust execution environment-Operation System, which could be impressive for non-hardware specialists, conditional on the base applicable from trust execution environment Operation System vendors. This research considers a simulation-based model (T-simulation) that cuts down the composition time and hardware background appropriate to frame a hardware situation for expectation execution situation prototyping.